3-Substituted N-Benzylpyrazine-2-carboxamide Derivatives: Synthesis, Antimycobacterial and Antibacterial Evaluation - Semelková, Lucia; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Navrátilová, Lucie; Trejtnar, František; Kubíček, Vladimír; Kuneš, Jiří; Doležal, Martin; Zitko, Jan (Molecules (Basel, Switzerland), 2017)
A series of substituted N-benzyl-3-chloropyrazine-2-carboxamides were prepared as positional isomers of 5-chloro and 6-chloro derivatives, prepared previously. During the aminolysis of the acyl chloride, the simultaneous substitution of chlorine with benzylamino moiety gave rise to N-benzyl-3-(benzylamino)pyrazine-2-carboxamides as side products, in some cases. Although not initially planned, the reaction conditions were modified to populate this double substituted series. The final compounds were tested against four mycobacterial strains. N-(2-methylbenzyl)-3-((2-methylbenzyl)amino)pyrazine-2-carboxamide (1a) and N-(3,4-dichlorobenzyl)-3-((3,4-dichlorobenzyl)amino)pyrazine-2-carboxamide (9a) proved to be the most effective against Mycobacterium tuberculosis H37Rv, with MIC = 12.5 μg·mL-1. Compounds were screened for antibacterial activity. The most active compound was 3-chloro-N-(2-chlorobenzyl)pyrazine-2-carboxamide (5) against Staphylococcus aureus with MIC = 7.81 μM, and Staphylococcus epidermidis with MIC = 15.62 μM. HepG2 in vitro cytotoxicity was evaluated for the most active compounds; however, no significant toxicity was detected. Compound 9a was docked to several conformations of the enoyl-ACP-reductase of Mycobacterium tuberculosis. In some cases, it was capable of H-bond interactions, typical for most of the known inhibitors.
Keywords: buňky Hep G2; Anti-Bacterial Agents; benzylamines; simulace molekulového dockingu; Pyrazines; Staphylococcus epidermidis; Mycobacterium tuberculosis; Microbial Sensitivity Tests; Hep G2 Cells; Molecular Docking Simulation; Staphylococcus aureus; antibacterial activity; cytotoxicity; pyrazinamide derivatives; vztahy mezi strukturou a aktivitou; Humans; enoyl-ACP-reductase; antibakteriální látky; molecular docking; molekulární struktura; mikrobiální testy citlivosti; antimycobacterial activity; pyraziny; Structure-Activity Relationship; lidé; Molecular Structure